Extremely Rare Presentation of Pilonidal Sinus Disease in the Posterior Cranial Fossa of a 2-Year-Old Patient: A Case Report - Yacoub, Hamzeh; Aqel, Aya; Adas, Mohammed; Hjouj, Qais; Yacoub, Zaid; Yacoub, Rita; Dababseh, Hadi (Journal of Neurological Surgery Reports, 2025)
A 2-year-old female patient presented after experiencing a generalized tonic-clonic seizure accompanied by fever, followed by a loss of consciousness. She underwent an urgent right frontal external ventricular drain placement. Intraoperative cerebrospinal fluid analysis was negative for infectious patterns. MRI showed a predominantly cystic lesion in the midline posterior fossa, with a compressive mass effect. Subsequently, she underwent a suboccipital craniotomy for microscopic resection of a posterior cranial fossa lesion. Histopathology reported keratin flakes with severe active inflammation, and foreign body type giant cell reaction in scalp excision with free hair shafts through the inflammatory focus, consistent with pilonidal sinus. The patient was then discharged home in good health.
Keywords: pilonidal sinus; cranial cystic lesion; posterior cranial fossa; pediatric neurosurgery